Rangelands Vegetation under Different Management Systems and Growth Stages in North Darfur State, Sudan (Range Attributes) - Mohamed, Mohamed AAMA; El Hag, Faisal Mohamed Ahmed; Elnour, Ibrahim Ali (International Journal of Environment, 2014)
This study was conducted at Um Kaddada, North Darfur State, Sudan, at two sites (closed and open) for two consecutive seasons 2008 and 2009 during flowering and seed setting stages to evaluate range attributes at the locality. A split plot design was used to study vegetation attributes. Factors studied were management systems (closed and open) and growth stages (flowering and seed setting). Vegetation cover, plant density, carrying capacity, and biomass production were assessed. Chemical analyses were done for selected plants to determine their nutritive values. The results showed high significant differences in vegetation attributes (density, cover and biomass production) between closed and open areas. Closed areas had higher carrying capacity compared to open rangelands. Crude protein (CP) and ash contents of range vegetation were found to decrease while Crude fiber (CF) and Dry matter yield (DM) had increased with growth. The study concluded that closed rangelands are better than open rangelands because it fenced and protected. Erosion index and vegetation degradation rate were very high. Future research work is needed to assess rangelands characteristics and habitat condition across different ecological zones in North Darfur State, Sudan. DOI: http://dx.doi.org/10.3126/ije.v3i3.11093 International Journal of Environment Vol.3(3) 2014: 332-343